Editorial. Issue 4 (August 2016) - ABUTALEBI, JUBIN; CLAHSEN, HARALD
Abstract : This volume of BLC presents two thematic sets of studies, the first one consisting of short concise reviews of studies on neuroimaging of the bilingual brain, and the second one a Special Issue edited by Margaret Deuchar that focuses on code switching, priming, and other cross-language effects in bilingual production and comprehension, presenting novel findings from different language combinations and a range of experimental and naturalistic methods; Deuchar (2016 ) provides an overview of this set of studies.